Potential Causes of Anti‐Phase Summer Precipitation Variability Between the Middle and Lower Reaches of the Yangtze River - Yuwei Zhou; Ge Liu; Xiaolu Yan; Sulan Nan; Ting Zhang; Yinghan Sang; Xuefeng Han; Yuhan Feng; Hancheng Zou (International Journal of Climatology, 2026)
Summer precipitation in the middle and lower reaches of the Yangtze River generally shows synchronous variability and is thus extensively studied as a unified climatic region. However, out‐of‐phase variations occur between the middle and lower reaches in some years. This study investigates the mechanisms of the positive middle Yangtze River precipitation (MYRP)–negative lower Yangtze River precipitation (LYRP) pattern from the perspectives of atmospheric circulation and land‐ocean thermal anomalies. The results suggest that a non‐canonical Silk Road Pattern (SRP) teleconnection in the upper troposphere, coupled with a mid‐to‐lower tropospheric anomalous anticyclone over Northeast Asia and a weakened western Pacific subtropical high (WPSH), contributes to this precipitation pattern. Further analysis reveals that colder‐than‐normal land thermal anomalies in the Greater Caucasus Mountains and the northeastern Tibetan Plateau, as well as warmer‐than‐normal sea surface temperature anomalies (SSTAs) in the Sea of Japan, may help maintain the SRP‐like Rossby wave train (SLWT), therefore influencing the positive MYRP–negative LYRP pattern. Linear baroclinic model sensitivity experiments further support the identified thermal anomalies can excite and maintain the SLWT. Given that the SLWT differs to some extent from the classical SRP in both wave source and downstream structure, this study also proposes a SLWT index based on 200‐hPa vorticity anomalies. This index effectively captures both the spatial structure of the SLWT and its link with out‐of‐phase precipitation anomalies between the middle and lower reaches of the Yangtze River and may serve as a potential indicator for the occurrence probability of the positive MYRP–negative LYRP pattern. These findings may improve our understanding of regional precipitation mechanisms in the Yangtze River basin, thereby providing a scientific basis for improved disaster prevention and mitigation strategies.